The influence of transparency and accountability of financial statements on the level of trust of Muzakki at the Amil Zakat, Infaq and Shadaqah Institution of Nahdatul Ulama Nusa Tenggara Barat - Fatmawati, Fatmawati; Nurmayanti, Eka (International Enterprise Integration Association, 2025)
This study aims to determine whether transparency and accountability affect the level of muzakki trust in amil zakat institutions at the Amil Zakat Infaq, Shadaqah Nahdatul Ulama Institute of Nusa Tenggara Barat. This type of research is a quantitative approach with primary data where the data collection method uses a questionnaire method distributed within the scope of LAZISNU NTB. The independent variables in this study are Transparency (X1) and Accountability (X2) and the dependent variable is Muzakki Trust (Y). The sample method used is nonprobability sampling, and there are 61 respondents. The data analysis technique used is multiple linear regression. The results of this study indicate that partial transparency has no significant effect on muzakki trust can be seen from the r test count on the variable relationship of 1.157 with a significant 0.252> 0.005, Accountability partially has a positive and significant effect on muzakki trust in the amil zakat infaq and shadaqah Nahdatul Ulama Nusa Tenggara Barat can be seen from the t test count on the variable relationship of 3. 233 with a significant 0.002 <0.005, transparency and accountability seen from the F test counted 34,294 with a significance of 0.000 simultaneously have a positive and significant effect on muzakki trust in amil zakat institutions, infaq and shadaqah nahdatul ulama Nusa Tenggara Barat.